PERTIMBANGAN MASLAHAT DALAM PUTUSAN PERCERAIAN AKIBAT KEKERASAN DALAM RUMAH TANGGA DI PENGADILAN AGAMA - Asni Asni (AHKAM : Jurnal Ilmu Syariah, 2014)
The Mashlahah Consideration in Divorce Cases Caused by Domestic Violence in Religious Court. The focus of this study is the consideration of mashlahah in the judge’s verdict in the settlement of domestic violence divorce cases in the Religious Court in Kendari, North Sulawesi. The results of this study shows a significant number of divorce cases are caused by domestic violence. This study also finds that the judge provided the decision based on formal and material legal considerations, facts of the court session, as well as consideration of mashlahah. But in considering mashlahah altogether it is formulated generally which should require an indepth analysis, through the principles of maqâshid al-syarî’ah.DOI: 10.15408/ajis.v14i1.1247